Conception of improving the sphere of waste handling in Ukraine on innovative principles - Shaho, Ye. P.; Krainov, I. P.; Bondar, O. I.; Maliovanyi, M. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The analysis of the state of handling waste system in Ukraine is conducted in the paper. Conception of improving the sphere of waste handling in Ukraine is offered that can be realized at the state level by creation of government monopoly of the technological and technical providing of waste recycling.